Implementasi Manajemen Pelaksanaan Supervisi Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pendidikan Agama Di MTS Negeri 2 Bengkalis - Sakri Sakri (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
One of the efforts to overcome teacher problems in learning is by educational supervision. Supervision is guidance in the form of guidance or guidance towards improving the educational situation in general and improving the quality of teaching and learning. Supervision is carried out by the Principal (supervisor) whose role is to supervise teaching and learning activities, teacher performance etc. The purpose of supervision is to develop better situations to train the learning process and improve the teaching profession. The study was conducted because researchers wanted to get a better understanding of a special case This research reveals specifically about the implementation of teaching supervision and teacher performance in the learning process of Islamic religious education in MTSN 2 Bengkalis. Based on the entire series of analysis and discussion of data, it can be concluded that the implementation of principal supervision of the performance of Islamic religious education teachers in MTSN 2 Bengkalis is The planning of principal supervision is carried out in a planned, systematic and continuous manner. At this stage the principal determines the name of the teacher to be observed, forms a determination of the time for the implementation of the observation time, compiles an observation grid and determines whether the class observation is known to the teacher or not, this is based on an agreement between the principal and the Islamic religious education teacher. In the implementation of supervision, the principal's attitude did not interfere with the process of learning Islamic religious education in the classroom even the principal at the end of class hours gave motivation to students to continue learning diligently. In the follow-up stage, the results of supervision are discussed jointly between Islamic religious education teachers and school principals who discuss teacher deficiencies in teaching in the hope that in the future teachers can improve them.